From teatime cookies to rain-pants: resolving dilemmas through design using concerns at three abstraction levels. Issue 3 (2nd October 2018) - Ozkaramanli, Deger; Desmet, Pieter M. A.; Özcan, Elif
Abstract: Users often have conflicting concerns (i.e., dilemmas), such as 'embracing change vs. following tradition.' Design can resolve these dilemmas through simultaneously fulfilling conflicting user concerns. This paper proposes three abstraction levels for framing user concerns when formulating dilemmas. In a large-scale industry project, we identified that dilemmas can be formulated and resolved at different abstraction levels. Based on these preliminary findings, we developed a structured way to formulate dilemmas, which involves using three different types of concerns (i.e., product-, activity-, and identity-focused concerns). In this framework, product-focused concerns represent the most concrete concern level and identity-focused concerns represent the most abstract level. Sixty master-level design students were asked to formulate a dilemma evoked by a product of their own choice and to create design ideas to resolve this dilemma. The results showed that dilemmas involving all concern levels can be an input for ideation, with the 'most abstract yet informative' dilemma being the most inspiring. In addition, we found that design can resolve dilemmas in several distinct ways, where each dilemma-resolving strategy comes with opportunities and challenges. Consciously formulating and examining alternative dilemma formulations can create opportunities that might otherwise not be considered as input for ideation.